Complying with 60 days' time-frame under Section 20(1) of the Industrial Relations Act during COVID-19 - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (LexisNexis, 2020)
An employee alleging dismissal without just cause or excuse will have to comply with certain statutory requirements before his claim may be referred to and adjudicated in the Industrial Court. This includes, inter alia, the sixty days statutory limitation period in s 20(1) of the Industrial Relations Act 1967 (‘the IRA’). The dismissal date would be obvious in a direct dismissal as the dismissal is initiated by the employer either with or without notice. However, in a constructive dismissal the date of the dismissal is subjective1 Generally, it would begin from the moment the employee resigns or quits employment due to the fact that the employer had breached the fundamental term of the employment contract. In either case, the employee must ensure that his representations under s 20(1) of the IRA is lodged at the Industrial Relations Department nearest to his place of residence within the statutory 60 days period. Failure to do so would jeopardise the dismissed worker’s claim for reinstatement under the IRA.